Intensive agriculture, a pesticide pathway to >100 m deep groundwater below dryland agriculture, Cordoba Pampas, Argentina - Cabrera, Agustín (2024)
Groundwater pesticide pollution in shallow groundwater is a well-established global phenomenon. However, deep aquifers are widely thought to be naturally protected from such modern contaminants, by confining geological barriers and upwards hydraulic gradients. Here we document pervasive pesticide pollution in >100 m deep artesian wells in a sedimentary aquifer below dryland agriculture. The vertical distribution of key groundwater markers, including numbers and concentrations of pesticides, stable (δ18O & δ2H) and radioactive (3H & 14C) isotopes and ion concentrations were used to develop a conceptual model of pollutant transport to deep groundwater. Tritium, stable isotope and pesticide distributions in unconfined groundwater indicate that water table rise to <1 m below the surface (due to anthropogenic landscape modification and periodic flooding), has created a rapid pollutant ‘doorway’ to groundwater. Despite a lack of deep borehole pumping for irrigation, these rising water tables have permanently inverted previously upward hydraulic gradients towards the underlying semi-confined aquifer in some areas. Physical heterogeneities and/or leaky domestic boreholes then act as preferential transport avenues for surface pollutants to both unconfined and semi-confined groundwater. These pathways allow small aliquots of highly contaminated surface water and modern unconfined groundwater to mix with the pre-existing pre-modern deep groundwater, resulting in mixed isotopic signatures in deep wells (e.g., radiocarbon <5 pMC but detectable tritium) and detections of multiple synthetic pesticides in the deep aquifer, including AMPA at concentrations up to 4.93 µg/L and Metolachlor up to 0.015 µg/L. Our results demonstrate how semi-confined deep groundwaters may be contaminated by current agricultural techniques even where deep groundwater exploitation is limited. We urge measures to eliminate these pollutant pathways.